Evaluating challenges of teaching and learning of english first additional language reading comprehension in primary schools : case study of Mahlohlwani Primary School, Malamulele North-East Circuit, Limpopo Province - Maluleke, Nkoka Champman (My University, 2022)
In rural South Africa (SA), poor reading comprehension skills in English First Additional Language (EFAL) are still found to be the main cause of poor academic achievement. For learners to comprehend the target language they must master the basic reading skills. This remains to be a great challenge for the rural schools in Limpopo. Rural learners are barely exposed to the language of the school, and they hardly have access to the EFAL reading materials or other learning aids. This study aims to evaluate the challenges that are faced in teaching and learning reading comprehension in rural primary schools in SA. This research study was framed by Cognitive constructivism and Schema theory in teaching and learning reading comprehension. A qualitative case study research design was adopted in the study. The sampled participants (one educator and 10 learners) were purposively selected to give answers to the research questions. The following data gathering techniques were used; observational field notes to gather data from the classroom context during the reading lessons, focus group interviews were conducted with the grade 6 learners, lastly, one educator was interviewed. The results prove the educators and learners are still facing challenges in the teaching and learning of EFAL. The study recommends, that the Department of Education intervenes by conducting more training workshops for the educators and parental involvement is encouraged as well for parents to be part of their children's educational journey.
Thesis (M.A. (English Studies)) -- University of Limpopo, 2022
Keywords: Teaching and learning; Mahlohlwani Primary School; Malamulele north -east circuit; Limpopo Province; Evaluating challenges; Reading Comprehension; Rural Schools; Reading -- Ability testing; Academic achievement -- South Africa -- Limpopo; Education, Primary -- South Africa -- Limpopo; English language -- Study and teaching; Reading comprehension -- Study and teaching